Alexithymia and avoidance coping following traumatic brain injury. - Rodger Wood (Journal of Head Trauma Rehabilitation., 2012)
Background: Individuals who develop maladaptive coping styles after traumatic brain injury (TBI) usually experiencedifficulty expressing their emotional state, increasing the risk of psychological distress. Difficulties expressingemotion and identifying feelings are features of alexithymia, which is prevalent following TBI. Objective: To examinethe relations among coping styles, alexithymia, and psychological distress following TBI. Participants: Seventy-onepatients with TBI drawn from a head injury clinic population and 54 demographically matched healthy controls.Main Measures: Toronto Alexithymia Scale-20, Estonian COPE-D Inventory, Beck Depression Inventory-II, andBeck Anxiety Inventory. Results: The participants with TBI exhibited significantly higher rates of alexithymia andpsychological distress and lower levels of task-oriented coping than healthy controls. Levels of avoidance copingand psychological distress were significantly higher in a subgroup of TBI patients with alexithymia than in a nonalexithymicTBI subsample. There were significant relations among alexithymia, avoidance coping, and levels ofpsychological distress. Regression analysis revealed that difficulty identifying feelings was a significant predictor forpsychological distress. Conclusion: Early screening for alexithymia following TBI might identify those most at riskof developing maladaptive coping mechanisms. This could assist in developing early rehabilitation interventions toreduce vulnerability to later psychological distress.